Significance of Salivary miRNA 21 Determined by Real Time PCR in Patients with Squamous Cell Carcinoma - Edan, Wisam Hamid; El-Samarrai, Sulafa Khalid (Journal of Baghdad College of Dentistry, 2016)
Background: Salivary biomarkers, a non-invasive alternative method to serum and tissue based biomarkers and it is consider as an effective modality for early diagnosis. Salivary microRNA 21, a nucleotide biomarker, was reported to increase in patients with oral squamous cell carcinoma. This study was conducted to measure the fold change of microRNA 21 in stimulated saliva and to study its association with smoking and occurrence of oral squamous cell carcinoma. Materials and methods: A 20 patients with oral squamous cell carcinoma who used to be smokers was included in addition to 40 control subjects (20 smokers and 20 non- smokers health looking subjects). Stimulated saliva was collected under standardized condition. Salivary microRNA 21 was assessed by real time PCR. Results: MicroRNA 21 fold change was significantly higher in both smoker patients with oral squamous cell carcinoma and in smoker control subjects compared to non-smoker control subjects. Conclusions: Salivary micrRNA21 can serve as a non-invasive tool aid in the diagnosis and follow up of squamous cell carcinoma patients.